Furio Jesi: Myth and Biography - Ruvituso, Mercedes (Escritura e Imagen, 2024)
When, in 1972, Furio Jesi first elaborated his model of the “mythological machine”, he started from a particular reading of the “myth of Rimbaud” and his legendary participation in the Paris Commune. However, in the context of May 1968, he also aims to question his own present: why do mythical epiphanies in the revolts of yesterday and today end in a “religio mortis”? This paper aims to “dismantle” the first formulation of the “mythological machine” in order to locate conceptually how it is constructed on the basis of the aporia between myth and “biography”. On the one hand, it will be shown that, in parallel to Guy Debord’s situationism, Jesi takes up, not always explicitly, certain places common to Walter Benjamin’s task of demythologisation: childhood, the commodity, revolt. On the other hand, the conceptual tension between myth and biography that redefines the distinction between bios and zoé will be interpreted as an equally “biographical” response to Karl Kerényi.